Lower Coated-Platelet Levels Are Associated With Increased Mortality After Spontaneous Intracerebral Hemorrhage. Issue 7 (July 2015) - Prodan, Calin I.; Stoner, Julie A.; Dale, George L.
<x xml:space="preserve">Abstract</x> Background and Purpose— Coated-platelets are highly procoagulant platelets observed on dual-agonist stimulation with collagen and thrombin. Coated-platelet levels are decreased in patients with spontaneous intracerebral hemorrhage when compared with controls and inversely correlated with bleed volume. We sought to investigate whether coated-platelets are associated with increased mortality at 30 days after spontaneous intracerebral hemorrhage. Methods— Coated-platelet levels were assayed in 95 consecutive patients with spontaneous intracerebral hemorrhage. The main outcome was mortality at 30 days according to coated-platelet levels at enrollment. Subjects were grouped into tertiles of the observed coated-platelet level distribution. Groups defined by tertile of coated-platelet level were compared using either ANOVA or a Kruskal–Wallis test for small group size for continuous measures and an exact Cochrane–Armitage trend test for categorical measures. Logistic regression was used to estimate the adjusted odds of death within 30 days associated with coated-platelet levels. Results— Cumulative mortality at 30 days was 23% (22 subjects). Mortality at 30 days differed among the coated-platelet tertiles: 44% for the first tertile (lowest coated-platelet levels), 19% for the second tertile, and 6% for the third tertile (trend test; P=0.0004). Logistic regression examining the association between mortality and coated-platelet levels showed that the odds of death at 30 days in those with levels <27% (n=47) were 6.83× the odds for patients with levels ≥27% (95% confidence interval, 2.10–22.23). Conclusions— These results support a link between impaired coated-platelet potential and outcome in intracerebral hemorrhage.